Is Procalcitonin Useful in Early Diagnosis of Serious Bacterial Infections in Children? - Gupta, Rakesh; Singh, Veena; Patrikar, Seema; Hazra, Nandita; Mathai, S S (Journal of Nepal Paediatric Society, 2013)
Introduction: Diagnosis of bacterial infections remains one of the greatest challenges in medical science, especially in children, in whom clinical signs are often nonspecific. The currently used sepsis screen has poor predictive value. Recently introduced marker procalcitonin (PCT) with high sensitivity and specificity is evaluated as early marker of serious bacterial infection in children. Materials and Methods: Children up to 5 years of age presenting with features of Systemic Inflammatory Response Syndrome(SIRS) were evaluated clinically and underwent standard sepsis screen namely total leukocyte count (TLC), peripheral blood smear for band count, C-reactive Protein (CRP) and newer tests like procalcitonin (PCT) and Interleukin-8 (IL-8). Results were analyzed using SPSS14.0. Results: One hundred patients suspected of sepsis were evaluated. Maximum cases were below one year (37%) with mean age of 27 months. Male:female ratio was 1.5:1. Respiratory system was the commonest system involved in (54%) followed by gastrointestinal (20%), genitourinary (10%) and central nervous system (5%). Seventy two cases were found to have confirmed sepsis, proven by blood culture (34%) and other investigations. Fifty two cases were diagnosed by conventional markers, while newer markers in 60 cases. Diagnostic evaluation revealed that newer markers have higher sensitivity and specificity as compared to conventional sepsis screen. Conclusion: Procalcitonin is a useful marker for diagnosis of serious bacterial infections in children and in combination with IL8 has a higher sensitivity and specificity as compared to standard sepsis screen. Therefore it is recommended that procalcitonin should be used for the screening of sepsis in children so that the treatment can be started earlier in order to prevent morbidity and mortality. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7988 J Nepal Paediatr Soc. 2013; 33(2):106-109